Internal Tremor in Long COVID May Be a Symptom of Dysautonomia and Small Fiber Neuropathy - Svetlana Blitshteyn; Ilene S. Ruhoy; Lauren R. Natbony; David S. Saperstein (Neurology International)
Background/Objectives: Internal tremor (IT) is often reported by patients with post-acute sequelae of SARS-CoV-2, also known as Long COVID, as a distressing and disabling symptom. Similarly, physicians are typically perplexed by the nature and etiology of IT and find it extremely challenging to manage. Methods: We describe a patient with Long COVID who experienced IT as part of post-COVID postural orthostatic tachycardia syndrome (POTS) and small fiber neuropathy (SFN) and review the limited literature available on this topic. Results: Our patient’s IT improved significantly after intravenous saline infusions, but there was no effect on IT with oral hydration, increased oral sodium chloride intake, neuropathic pain medications, muscle relaxants, or medications used for the treatment of POTS. Conclusions: Based on this case, our clinical experience, and the limited literature available to date, we believe IT is a manifestation of POTS and SFN, which may be driven by hypovolemia, cerebral hypoperfusion, sympathetic overactivity, neuropathic pain, and mast cell hyperactivation. Subjective description, objective findings, and diagnostic and therapeutic considerations in patients with IT and Long COVID are discussed.